Pig has a plan - Long, Ethan (New York : Holiday House, 2013)
Pig is trying to take a nap, but his friends are making all kinds of noise.
School Library Journal, September 2012
Publisher's Weekly, August 2012
Horn Book, April 2013
Choice, April 2013
Kirkus Review, June 2012
0.9
Keywords: Naps (Sleep) -- Juvenile fiction; Noise -- Juvenile fiction; Swine -- Juvenile fiction; Domestic animals -- Juvenile fiction; Naps (Sleep) -- Fiction; Noise -- Fiction; Pigs -- Fiction; Domestic animals -- Fiction; Naps (Sleep) -- Fiction; Noise -- Fiction; Pigs -- Fiction; Domestic animals -- Fiction; Readers (Elementary)